La Extinción de la Obligación Alimenticia al cumplimiento de los 21 años debe resolverse de Forma Directa y no Mediante Incidente - Gómez Lapo, Mirian Mercedes (2016)
The Constitution of the Republic of Ecuador, recognizes and guarantees in article 169 persons an access to justice quickly and efficiently because there are enshrined the procedural principles that must be met by the judicial authorities. Therefore, this work begins by addressing the issue from generalities where originates the right to food, as well as the origin of responsibility and attributed meaning to that expression in the different doctrinal analysis of the subjective element of the general theory of food required. Specifically, will try to prove that the concept designated by the expression "obliged to provide food," responds to a logical requirement of the adoption of the mandatory relationship as explanatory diagram of the general theory of food required. Ultimately, it will be prove that the extinction of the obligation to food has been processed through a trial of incidents; a study of the constitutional principles and the relevant legal regulations. Is an exhibition that is the extinction of the alimony; and who are the owners of this right is to say those who have the right to claim food; In particular, article has been especially Innumerado... 4 (129) in specifically paragraph 2 which says that adults or adults up to the age of 21 years (...). In the same way it is on 7 the presumption of the extinction of the right to food which is regulated by the innumerado 32 of the code of childhood and adolescence. However, the object of the work is not exhausted in the search for what is the obligation to food or what understands the legislator when it uses the expression required to provide pension, but, on the one hand, this work also aims to provide an analysis of all those supposed individuals who reflect the general concept adopted; and, on the other hand, offers an exhibition of the legal regime of the trial of food when it is directed against a liable to pay alimony in favour of one of the beneficiaries that determines the code of childhood and adolescence. Now, the study of food required is done is only from a procedural perspective. In addition to examining the legal regime from the point of view of its procedure, i.e., its budget home and legal consequences that generates its realization. From unit IV has reserved for the study of the procedural status of the contentious trial general foods, as well as the incidents both increase and decrease, which are directed against one of the obligors that determines the code of childhood and adolescence. As noted, this chapter only discussed what the prosecution produces against the obligor to the provision of alimony, ignoring other issues that are not own as they are the extinction of the food obligation, i.e. the procedure that must be followed to reach the resolution that's 8 terminate the obligation that has been raised against the alimony as have gone the circumstances that motivated the imposition of the obligation. In this sense, there has been an analysis between the legal act of extinction of the obligation to food, and the Judiciary Act of incidents of extinction that is processed within the legal specialized third women's unit, childhood and adolescence in the Canton of Loja. The reason for this distinction is that the action of extinction food is a right that has the recipient to complete this obligation, while the process that takes place is through incidents that is true in the legal regulations are not regulated; but the judicial authorities have believed convenient to process them through incidents by the simple fact that if alimony was fixed by a trial the logical thing would be that extinction to be treated also by a judgment, since this procedure is processed to the same competent authority that fixed pension except in cases of change of address. It is also about the legal nature of the resolutions, that while the process of extinction of the alimony has been observed launches since the submission of the demand to the resolution which ended the obligation to continue passing food to children over the age of 21